A Randomized Controlled Trial of Anti-TNF α Bio-similar Adalimumab vs. Prednisolone in the Management of Leprosy Patients with New Type 1 Lepra Reaction. (4th October 2017) - Mitra, Debdeep
Abstract: Background: Leprosy Type 1 (T1R) reactions are immune-mediated events leading to nerve damage and preventable disability affecting hands, feet and eyes. TNF-α is the main inflammatory cytokine associated. Type 1 Reactions are treated with oral corticosteroids. There is little evidence on alternative treatments for patients who do not respond to steroids or experience steroid adverse effects. We report the results of a randomized controlled trial testing the efficacy and adverse effect profile of Anti-TNF α Bio-similar Adalimumab and prednisolone in comparison to prednisolone only in patients with new T1R. Outcomes were measured using a clinical severity score, recurrence rate, adverse events and quality of life. Methods: Seventy-three patients with new T1R were randomized to receive Adalimumab or Prednisolone for 20 weeks. TNF-α levels were corelated before and after the intervention. Results: Recovery rates in skin signs was similar in both groups (91% vs 88%). Improvements in nerve function both, new and old, sensory (66% vs 49%) and motor (75% vs 74%) loss were higher (but not significantly so) in the patients on Adalimumab. Recurrences rates of T1R (85%) were high in both groups, and recurrences occurred significantly earlier (8 weeks) in patients Adalimumab, who needed 10% more additional prednisolone. Serious major and minor adverse events rates were much lesser with Adalimumab as compared with Prednisolone alone. Both groups had a significant improvement in their quality of life after the study, measured by the Short form survey SF-36. Conclusion: This is the first double-blind RCT assessing adalimumab, in the management of T1R. It could be a safe alternative second-line drug for patients with T1R who are not improving with prednisolone or are experiencing adverse events related to prednisolone. TNF-α levels could be an important diagnostic marker to diagnose and prognisticate cases of Type 1 Lepra reaction, which if not treated in time can lead to irreversible nerve damage. Disclosures: All authors: No reported disclosures.